Rabies in Children (An Eleven Years Retrospective Study in Medan) - Rafita Ramayati; Rusdidjas Rusdidjas; Helena Siregar (Paediatrica Indonesiana, 1982)
At the Department of Child Health Medical School University of NorthSumatera/Dr. Pirngadi Hospital Medan, a retrospective study for analysis onRabies in Children from 1977 - 1980 had been carried out. We found 29cases consisting of 23 males arul 6 females. The highest incidence was between 6 - 12 years. All was bitten by dogs.Lower limbs were the most common site of dog bite. Twenty of the 29cases were derived from Medan Munic~TJ!e. All of the cases did not receivedpost"exposure immunization. People's alertness to dog control is still unproperly practice and stray dogs are everywhere.